PENERAPAN FUZZY INFERENCE SYSTEM PEMILIHAN DESAIN INTERIOR - Nanda Jarti; Weni Lestari Putri (STMIK Royal, 2020)
Abstract: Interior design is currently growing. This can be seen from the various designs in each building. Each design has different characteristics and shapes. The problem that is often experienced by users is the lack of user knowledge in the field of interior design so that after the design is finished, the user is not satisfied with the results of the interior design. The main objective of this research is a decision making system in selecting interior designs according to user needs by paying attention to criteria such as design form, design size, material and quality. The method of selecting interior design using the Mamdani method. The mamdani method is very suitable in calculating the output value of each criterion value and the end result becomes the reference value in making a decision. The resulting system is in the form of design selection criteria according to user needs. Thus the results of this study get an Output value of 427,368 which is in the range with the value considered. Keywords: fuzzy inference system; interior design; mamdani method; software matlab. Abstrak: Desain Interior saat ini semakin berkembang, Hal ini bisa dilihat dari berbagai desain pada setiap bangunan. Setiap desain memiliki karakteristik dan bentuk yang berbeda beda. Permasalahan yang sering dialami pengguna yaitu kurangnya pengetahuan pengguna dibidang desain interior sehingga setelah desain selesai dikerjakan pengguna tidak Puas dengan hasil desain interior. Tujuan utama penelitian ini berupa Sistem pengambilan keputusan dalam pemilihan desain interior sesuai dengan kebutuhan pengguna dengan memperhatikan kriteria seperti Bentuk Desain, ukuran desain, bahan dan Kualitas. Metode pemilihan Desain interior menggunakan metode Mamdani. Metode mamdani sangat cocok dalam menghitung nilai output dari masing masing nilai kriteria dan hasil akhirnya menjadi nilai acuan dalam pengambilan sebuah Keputusan. Sistem yang dihasilkan berupa kriteria pemilihan desain sesuai kebutuhan pengguna. Dengan demikian Hasil penelitian ini mendapatkan nilai Output sebesar 427.368 yang berada pada range dengan nilai dipertimbangkan. Kata kunci: desain interior; fuzzy inference system; metode mamdani; software matlab.